Determination of Profitability: Analysis of Non-Revenue Water, Legal Aspects, Cost of Goods Sold, Chemicals, Custome Behavior, and Government Regulations (Study Literature Review) - Adam, Helmi; Budi, Herwanto (International Journal of Advanced Multidisciplinary, 2025)
The purpose of this literature review is to develop hypotheses for future researchers conducting research related to profitability. The research article on determining profitability: analysis of non-income water, legal aspects, cost of goods sold, chemistry, customer behavior, and government regulations is a scientific literature article in the field of operational management. The approach used in this literature review is descriptive qualitative. The data collection technique used is literature study or reviewing previous relevant articles. The data used in this study is secondary data with a maximum publication of 8 years, sourced from academic online media such as Thomson Reuters Journal, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. Empirical data was used to support the phenomena observed in this study. In this study, one relevant previous study was used for each variable to review the results of the previous study. The results of the literature review are as follows: 1) Non-revenue water affects profitability; 2) Legal aspects affect profitability; 3) Cost of goods sold affects profitability; 4) Chemicals affect profitability; 5) Customer behavior affects profitability; and 6) Government regulations affect profitability.